126 Anatomy of Cerebellar Mutism: Reduced Fractional Anisotropy in the Superior Cerebellar Peduncle. (1st August 2016) - McEvoy, Sean D.; Lee, Amy; Ojemann, Jeffrey G.; MacDonald, Christine
Abstract: INTRODUCTION: Cerebellar mutism is a common finding after resection of cerebellar tumors, especially in children. It has been reported to occur in up to 39% of posterior fossa tumor resections. Once thought to be a transient finding, a growing body of evidence has associated it with long-term neurological sequelae. The pathophysiology and anatomy of this phenomenon remains controversial. METHODS: All patients with cerebellar tumors undergoing resection at Seattle Children's Hospital from June 2010 to June 2015 were retrospectively reviewed. Each patient underwent a diffusion tensor imaging-sequenced MRI of the brain as part of his/her postresection imaging. Cerebellar mutism was defined in patients who were awake and without focal deficit but unable to produce more than single words and eventually recovered fluent speech. Patients with cerebellar mutism were compared with postresection patients who had fluent speech with no language deficit and patients who had fluent speech with mild language deficit. RESULTS: Seven patients (17%) met criteria for postoperative cerebellar mutism. Eighteen patients (43%) had fluent speech with mild language deficit, and 17 patients (40%) had fluent speech with no language deficit. Fractional anisotropy (FA) was markedly reduced in the superior cerebellar peduncle (SCP) ( P = .01) of patients who had cerebellar mutism compared with both groups of verbally fluent patients. No changes where seen in mean diffusivity (MD), radial diffusivity (RD), or axial diffusivity (AD) of the SCP. No changes where seen in FA, MD, RD, or AD in the middle cerebellar peduncle, inferior cerebellar peduncle, or the white matter of the cerebellum. CONCLUSION: Patients with cerebellar mutism showed marked changes in the FA of the SCP. No changes where seen elsewhere in the cerebellum. These changes may not be seen with conventional MRI techniques that do not use DTI sequences.